The Asia Crisis : Causes, Policy Responses, and Outcomes - Berg, Andrew (IMF Working Papers; Working Paper, 1999)
This paper tells the story of the Asian financial crisis by addressing four questions: What were the causes of the crisis, how did the crisis unfold, what were the policy responses, and what have been the outcomes? The paper takes the view that none of these questions can be understood without appreciating the fundamental vulnerabilities that left authorities without effective tools to counter sudden capital outflows. The pattern of output decline suggests that these vulnerabilities, particularly weaknesses in domestic financial systems, played a larger role than tight monetary policy in determining outcomes.